Increasing Production Capacity and Financial Strengthening of Hand-Printed Batik Motif Textile Business at Kenayyu SME in Sragen Regency - Murni, Sri; Kurniadi, Edi; Hisjam, Muhammad; Rahmawati, Rahmawati; Rudianto, M (IMPOWERMENT SOCIETY, 2025)
This community service program aims to address the problems faced by Kenayyu Small and Medium Enterprises (SMEs) in Sragen Regency, particularly in the areas of financial management, accounting practices, design innovation, production capacity, and marketing. The urgency of this activity arises from the limited availability of production equipment, unstructured financial recording systems, and lack of marketing strategies, which hinder the competitiveness and sustainability of hand-printed batik businesses. To overcome these issues, the program was implemented through five main stages: (a) socialization, (b) training, (c) technology application, (d) mentoring and evaluation, and (e) program sustainability. The socialization stage built awareness and commitment among partners, while the training improved skills in financial recording, accounting applications, and batik motif design. The application of technology was carried out through the use of dynamo-powered equipment to enhance production efficiency. Mentoring and evaluation ensured continuous improvement and problem-solving, and the sustainability stage encouraged partners to maintain progress after the program ended. These activities have produced significant outcomes, including increased financial literacy, better product design innovation, improved production efficiency, and expanded digital marketing through marketplaces, leading to higher competitiveness and turnover for partner SMEs.